Typification and synonymizations in Jatropha martiusii (Euphorbiaceae) - Moreira, Ariane Dos Santos; Da Silva, Otávio Luis Marques; Cordeiro, Inês; Torres, Daniela Santos Carneiro (Phytotaxa, 2023)
Jatropha Linnaeus (1753: 1006) belongs to subfamily Crotonoideae (Euphorbiaceae) and has ca. 180 species distributed in tropical and subtropical regions of the world (Dehgan 2012; Webster 2014). The genus is found throughout the Neotropical region, with Mexico (50 spp.) and Brazil (23 spp.) as its centers of diversity (Christensen et al. 2019).